Ion-Incorporative, Degradable Nanocellulose Crystal Substrate for Sustainable Carbon-Based Electronics - Thi, Quyen Vu; Ko, Jaehyoung; Jo, Yerin; Joo, Yongho (American Chemical Society, 2022)
Electronic wastes from transient electronics accumulate biologically harmful materials with global concern. Recycling these wastes could prevent the deposition of hazardous chemicals and toxic materials to the environment while saving scarce natural compounds and valuable resources. Here, we report a sustainable electronic device, taking advantage of carbon resources and a biodegradable cellulose composite. The device consists of an ambient-stable carbon nanotube as a semiconductor, graphene as electrodes, and a free-standing cellulose filter paper/nanocellulose composite as a dielectric layer. The dual-functional cellulose composite acting simultaneously as a robust substrate and a dielectric is demonstrated, which is compatible with solution device fabrication processes. An optimized channel dimension of 5 mm x 3 mm with the addition of ions that facilitates a charge transport realized a device with an on-current per width of 9.6 mu A mm(-1) , an on/off ratio > 10(2), a field-effect mobility of 2.03 cm(2) V-1 s(-1), and long-term stability over 30 days under ambient conditions. Successful separation of the carbonaceous components via an eco-friendly solution sorting protocol allowed the recycled device to display excellent electronic performance, with a recapture efficiency of 90%. This effort demonstrates a processable, lowcost, and sustainable electronic system that can be applied in the current realm of the semiconducting and sensing industry.